Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1001/archneurol.2009.336
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography–Computed Tomography in Paraneoplastic Neurologic Disorders

Abstract: To evaluate the cancer detection rate of wholebody positron emission tomography-computed tomography (PET-CT) in a paraneoplastic neurologic context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 38 publications
4
80
1
3
Order By: Relevance
“…Seronegativity for paraneoplastic antibodies does not exclude a diagnosis of cancer, and testing for occult malignancy should proceed in highly suspicious cases. 5 The low positivity rates for most paraneoplastic antibodies in this study are consistent with their rarity, and reflects the ordering of this testing in patients with diverse neurologic presentations, where no cause has been established. 1 The more frequent detection of NMO-IgG and NMDA receptor antibody is consistent with the more narrow clinical contexts for ordering these 2 tests.…”
Section: Resultssupporting
confidence: 72%
“…Seronegativity for paraneoplastic antibodies does not exclude a diagnosis of cancer, and testing for occult malignancy should proceed in highly suspicious cases. 5 The low positivity rates for most paraneoplastic antibodies in this study are consistent with their rarity, and reflects the ordering of this testing in patients with diverse neurologic presentations, where no cause has been established. 1 The more frequent detection of NMO-IgG and NMDA receptor antibody is consistent with the more narrow clinical contexts for ordering these 2 tests.…”
Section: Resultssupporting
confidence: 72%
“…If findings on CT of the chest, abdomen, and pelvis are negative, 18 F-fluorodeoxyglucose-positron emission tomography or combined positron emission tomography and CT may identify the underlying tumor. 27,81 In some instances, the PNS and associated antibodies may sufficiently suggest a particular cancer to prompt diseasespecific imaging modalities such as mammography. If, despite these studies, no malignancy is identified, it has been recommended that clinical and radiographic surveillance be repeated every 3 to 6 months for 2 to 3 years.…”
Section: Paraneoplastic Neurologic Syndromesmentioning
confidence: 99%
“…The details of the study design, patient demographics and characteristics, paraneoplastic presentation, paraneoplastic antibody status, index test, proportion of patients diagnosed with underlying malignancy, and reference standards of each included study were summarized in Supplemental Tables 2 and 3 (3,5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(28)(29)(30)(31). Among the 24 studies included in the qualitative assessment, 4 studies were prospective and 20 studies were retrospective.…”
Section: Study Characteristics and Methodologic Quality Assessmentmentioning
confidence: 99%
“…Three studies did not clearly describe the reference standard used in patients with negative 18 F-FDG PET/CT results and were not included in the quantitative analysis (29,30,36).…”
Section: Study Characteristics and Methodologic Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation